PENGARUH PENGGUNAAN MICROSOFT EXCEL TERHADAP EFEKTIVITAS KERJA KARYAWAN DENGAN VALIDITAS DATA KEBERANGKATAN DAN KEDATANGAN PESAWAT SEBAGAI VARIABEL INTERVENING DI TERMINAL OPERASIONAL CENTER PT. ANGKASA PURA II SOEKARNO-HATTA - ZAIDAN SABILUDDIN; Amelia Puspa Tamara (Jurnal Manajemen Dirgantara, 2024)
The effectiveness of employee work in airline companies is strongly influenced by the validity of aircraft departure and arrival data. This study found that the use of Microsoft Excel alone has no significant influence on employee work effectiveness without the validity of departure and arrival data as an intervening variable. Valid data, which is data that is accurate, detailed, and has minimal errors, plays a key role in improving employee work effectiveness. The use of Microsoft Excel becomes significant in improving work effectiveness only when the validity of departure and arrival data is considered. This is evidenced by the results of the study showing a significance value of 0.00 <0.05 and a T-test between Microsoft Excel and employee work effectiveness of 0.0448, which indicates no significance without intervening variables. However, with the validity of departure and arrival data as an intervening variable, the T-test value increases to 0.001, and the Sobel test shows a significant effect with a T-count value of 6.190 > 2.052. The coefficient of determination (R2) of 0.929 indicates that 92.9% of the variability in employee work effectiveness can be explained by the relationship between the independent and dependent variables. Thus, the validity of aircraft departure and arrival data is an important factor in maximizing employee work effectiveness through the use of Microsoft Excel at the terminal operations center of PT Angkasa Pura II Soekarno-Hatta.